2016
DOI: 10.3892/or.2016.5196
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-574 in cancer stem cells causes recurrence of prostate cancer via targeting REL

Abstract: miR‑574‑5p has been reported involved in the pathogenesis of numerous human malignancies such as colorectal and lung cancer. In this study, we aimed to explore the roles of REL and miR‑574 in the recurrence of prostate cancer (PCa) and to identify the underlying molecular mechanisms. Our literature search found that miR‑574 is regulated in cancer stem cells (CSCs), and next we used the microRNA (miRNA) database (www.mirdb.org) to find REL as a target of miR‑574. Luciferase assay was performed to verify the miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous reports showed that miR-744 and miR-574 played role in inhibition of cell proliferation and invasion or tumor-suppressive in different human malignancies, which might be novel and efficient therapeutic targets [80,81,82]. In addition, miR-574 also could inhibit apoptosis [83]. On comparing PPR vaccine virus and PPR virulent virus, the miR-30 and let-7 family were commonly differentially expressed in spleen and lung tissues of goats infected with PPR virulent virus in vivo at 10 dpi, PBMC of goat infected with PPR virulent virus in vivo at 9 dpi, PBMC of goat inoculated with PPR vaccine virus in vitro at 1 dpi, and PBMC of sheep inoculated with PPR vaccine virus in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that miR-744 and miR-574 played role in inhibition of cell proliferation and invasion or tumor-suppressive in different human malignancies, which might be novel and efficient therapeutic targets [80,81,82]. In addition, miR-574 also could inhibit apoptosis [83]. On comparing PPR vaccine virus and PPR virulent virus, the miR-30 and let-7 family were commonly differentially expressed in spleen and lung tissues of goats infected with PPR virulent virus in vivo at 10 dpi, PBMC of goat infected with PPR virulent virus in vivo at 9 dpi, PBMC of goat inoculated with PPR vaccine virus in vitro at 1 dpi, and PBMC of sheep inoculated with PPR vaccine virus in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study by Hu J. et al showed that miR-93 is a key regulator of EZH1 as well as JAK1, STAT3, AKT3, SOX4, and HMGA2 in breast cancer stem cells [ 108 ]. In a study of prostate cancer stem cells, Lai et al reported miR-574-5p depletion along with EZH1 and REL increased levels [ 109 ].…”
Section: Epi-mirnas and Histone Modification Machinery In Cancermentioning
confidence: 99%
“…For example, microRNA-547 has been reported to inhibit apoptosis and may be a novel prognostic and therapeutic target in the management of PCa recurrence. [ 5 ] Another microRNA, microRNA-96, was shown to promote the growth of PCa cells by suppressing MTSS1. [ 6 ] Another type of RNAs, that is, long noncoding RNAs (lncRNAs), are the focus of intensive research as current data suggest their potential in cancer diagnosis, prognosis, and therapy.…”
Section: Introductionmentioning
confidence: 99%